INOVASI PELAYANAN PUBLIK BERBASIS WEBSITE SIKARANNUANG DI KANTOR KECAMATAN PANAKKUKANG KOTA MAKASSAR - Adawiyah, Hazanatul; Wahid, Nur; Taufik, Ahmad (Universitas Muhammadiyah Makassar, 2024)
This study aims to find out how effective the Sikarannuang Website is in the Panakkukang District Office, Makassar City. This study uses a qualitative method with a descriptive type. The results of this research can be seen from the Relative Adventage Aspect (plus value), which shows that the Sikarannuang Website has more value compared to before and can be accessed anytime and anywhere. From the Compatibility aspect, it shows that the Sikarannuang Website is in accordance with what the community needs, namely improving public services. In terms of complexity, it shows that the Sikarannuang Website is usually constrained by networks and people who don't understand the use of cellphones. In terms of Observability, it shows that the Sikarannuang Website is easy to understand because it has a simple and easy-to-understand display. In terms of Triability (can be tried), it shows that the Sikarannuang Website is proven to be tried